Observations of kinetic scale field line resonances. Issue 2 (21st January 2014) - Chaston, Christopher C.; Bonnell, John W.; Wygant, John R.; Mozer, Forrest; Bale, Stuart D.; Kersten, Kris; Breneman, Aaron W.; Kletzing, Craig A.; Kurth, William S.; Hospodarsky, George B.; Smith, Charles W.; MacDonald, Elizabeth A.
Abstract We identify electromagnetic field variations from the Van Allen Probes which have the properties of Doppler shifted kinetic scale Alfvénic field line resonances. These variations are observed during injections of energetic plasmas into the inner magnetosphere. These waves have scale sizes perpendicular to the magnetic field which are determined to be of the order of an ion gyro‐radius (ρi) and less. Cross‐spectral analysis of the electric and magnetic fields reveals phase transitions at frequencies correlated with enhancements and depressions in the ratio of the electric and magnetic fields. Modeling shows that these observations are consistent with the excitation of field‐line resonances over a broad range of wave numbers perpendicular to the magnetic field (k⊥) extending to k⊥ρi ≫ 1. The amplitude of these waves is such that E/Bo ≳ Ωi/k⊥ (E, Bo, and Ωi are the wave amplitude, background field strength, and ion gyro‐frequency, respectively) leading to ion demagnetization and acceleration for multiple transitions through the wave potential.